1990
DOI: 10.1029/jd095id10p16755
|View full text |Cite
|
Sign up to set email alerts
|

Emission of nitric oxide (NO) from tropical forest soils and exchange of NO between the forest canopy and atmospheric boundary layers

Abstract: Emissions of NO from soils in the Amazon rain forest were measured at 66 locations (224 measurements) using an enclosure technique, and continuous vertical profiles of NO and 03 were measured between the ground and 41-m altitude. Fluxes of NO averaged 8.9 (+1.5) x 109 molecules crn -2 s -1 from the dominant (yellow clay) soils of the region, with larger fluxes (33.7 (_+6.5) x 109 molecules cm -2 s -1) observed from adjacent white sand softs. Fluxes from clay softs were lower by more than a factor of 5 than flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
86
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 44 publications
18
86
1
1
Order By: Relevance
“…Underpredicted NO and NO y concentrations in the model might, in turn, be related to underestimated NO emissions from tropical forests. Flux measurements have shown that soils have high emissions of NO x in the forested regions of both central Amazonia (40)(41)(42)(43) and southeast Asia (44). The above-soil NO x emission modeled in the CTM for the wet season of central Amazonia was 10 times lower than the observations reported in the literature (SI Appendix).…”
Section: Discussioncontrasting
confidence: 49%
“…Underpredicted NO and NO y concentrations in the model might, in turn, be related to underestimated NO emissions from tropical forests. Flux measurements have shown that soils have high emissions of NO x in the forested regions of both central Amazonia (40)(41)(42)(43) and southeast Asia (44). The above-soil NO x emission modeled in the CTM for the wet season of central Amazonia was 10 times lower than the observations reported in the literature (SI Appendix).…”
Section: Discussioncontrasting
confidence: 49%
“…Nitric oxide concentrations characteristic of central Amazonia range from 20 to 70 ppt (Torres and Buchan, 1988;Bakwin et al, 1990;Levine et al, 2015). Daytime maximum ozone concentrations are 10 to 15 ppb (Rummel et al, 2007).…”
Section: Background Compared To Polluted Conditionsmentioning
confidence: 99%
“…Bargsten et al, 2008). For vegetation higher than about 30 cm, the chamber height can easily be extended by an additional cylinder module (similar to Bakwin et al, 1990;Suh et al, 2006). Finally, the chamber system may also be used for indoor applications with a controlled environment, e.g.…”
mentioning
confidence: 99%
“…after rain events (Meixner et al, 1997), after cutting (Davison et al, 2008) or fertilisation (Bakwin et al, 1990). A variable number of individual chambers (e.g.…”
mentioning
confidence: 99%